Peran Strategi Digital Marketing dalam Meningkatkan Brand Awareness XOVID20 - Nyoman Sri Manik Parasari; Anggreswari, Ni Putu Yunita; Maheswari, Anak Agung Ari; Suanda, I Wayan Seven Wisnu Putra (Politeknik Negeri Ambon, 2025)
This research aims to analyze the digital marketing strategy implemented by Xovid20 in building brand awareness in the digital market. Using a qualitative approach, this research involves in-depth interviews with owners, designers, and consumers of Xovid20 products, as well as analysis of digital content shared by the brand. The results showed that Xovid20 successfully strengthened brand awareness through the utilization of social media, particularly Instagram, as the main platform for communication and marketing. The digital marketing strategy implemented focuses on creating creative content relevant to the brand identity, which is able to attract and maintain consumer engagement. Xovid20's success in building brand awareness is also supported by the consistency of themes and brand identity in every digital content they share. These findings provide valuable insights into the effectiveness of digital marketing in strengthening brand awareness in the digital era, and can serve as a reference for other companies in developing their marketing strategies.